The effect of Mechanical Vibration on the Heat Transfer and Flow Characteristics - Mustafa A. Jumaah; A.P. Kamal J. Tawfeeq (International Journal of Computational and Experimental Science and Engineering, 2025)
This review investigates the variations in flow characteristics and heat transfer performance of an annular chamber when subjected to longitudinal mechanical vibration. Considering previous research, the study demonstrates the thermal radiation induced by vibrations in engineering components, especially in heat exchangers. The research evaluates the effects of changes in vibration frequency, acceleration magnitude, and signal type on heat transfer rates and pressure drop in the annular opening. In addition, the vibration mechanism and flexible fins are investigated as alternative methods to enhance heat transfer by comparing the heat transfer coefficient between the baseline and optimal scenarios. Several studies have examined different flow configurations, spacing ratios, and flow regimes related to heat transfer and fluid dynamics around cylinders experimentally and numerically. Their results shed light on the diverse effects of spacing ratios and flow regimes on heat transfer and fluid dynamics. It is important to note that higher Reynolds numbers are associated with more uniform flow around cylinders without vortex shedding, possibly indicating the complexity within these networks. The present research is an extension of the convection of all types by vibrations, as it reveals the effect of vibration on the heat transfer performance of convection. This section presents a literature review to monitor the potential gaps in the literature related to the topic under discussion, which is helpful for further research.